How artificial intelligence (AI) is transforming tourism industry - Boon, Yi Jean (2024)
AI-driven big data analysis is transforming the tourism industry. This study focuses on AI's impact on the tourism industry from tourists' perspectives, filling a significant research gap. The general objective of this study is to examine how AI is transforming the tourism industry. With this aim, the primary data is collected through selfadministered questionnaires from a convenience sample of 402 respondents on different social media platforms. Besides, the IBM Statistics Package for Social Science (SPSS) is used to test the proposed hypotheses in this study and the Technology Acceptance Model (TAM) is utilized to investigate the implementation of chatbots and voice assistances, personalization and recommender systems, language translation applications, and device and integrated systems towards the transformation of tourism industry. Based on the findings of this study, it reveals that chatbots and voice assistants, personalization and recommender systems, language translation applications, and device and integrated systems have a positive significant relationship with transformation of tourism industry. As a conclusion for this study, ease of usage and usefulness of a new technology is crucial. Moreover, this study is offering valuable insights and practical recommendations based on tourist perspectives for industry practitioners. Hence, this study has the potential to contribute to the initiation of enhanced AI systems and tourism industry that fosters economic growth and enhances consumer satisfaction.